VCRs: The End of TV as Ephemera - (:unkn) unknown (My University, 2015)
Although the VCR is often written about in scholarly literature, it is usually discussed in relation to Hollywood videotapes and rental stores. This study fills a gap in the current literature by presenting a significant history of the VCR in relation to TV during the period regularly referred to as the VCR's first decade, 1975 to 1985. Specifically, this study is a look at the divergent discourses of the TV industry and the public opinion of TV viewership during this early era that offer insight into how we have come to contemporarily conceptualize TV. While the TV industry considered the VCR as a technology with the potential to disrupt their business, TV viewers interpreted the VCR as a way to take control of their hobby. Through the device's main uses, time-shifting and library building, TV viewing became an activity defined by viewers' choices, conveniences, and desire to preserve TV programs.
Keywords: History; Industry; Recording; Television; VCR; Video